Wayside Market, Trinidad - (:unkn) unknown (H.O. Thomas [Printed in Britain], 2009)
Locals sell their vegetables on vending stalls located along the roadside.
Colour: Black and white;Style:Landscape;Other:Bordered,Divided
Keywords: Postcards; Trinidad and Tobago; Street vendors; Markets; Vending stalls